2017
DOI: 10.1111/pcmr.12667
|View full text |Cite
|
Sign up to set email alerts
|

CXCL‐10 and Interleukin‐6 are reliable serum markers for vitiligo activity: A multicenter cross‐sectional study

Abstract: This cross-sectional multicenter study aimed to evaluate serum CXCL-10, as an activity marker for vitiligo, and compare it with other putative serum and tissue markers. Serum CXCL-10 was compared to interferon gamma (IFN-γ), interleukin 6 (IL-6), and IL-17 using ELISA in 55 non-segmental vitiligo patients (30 active and 25 stable) and 30 healthy controls. Marginal skin biopsy was taken for immunohistochemical evaluation of CD8+T cells and CXCL-10+ve cells. Serum levels of CXCL-10, IL-17, and IL-6 were elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 33 publications
(58 reference statements)
1
42
1
Order By: Relevance
“…Of initially identified 165 citations, 11 studies including 626 vitiligo patients and 475 controls were finally selected . The study selection process using PRISMA flow chart is shown in Figure , and the characteristics of the included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Of initially identified 165 citations, 11 studies including 626 vitiligo patients and 475 controls were finally selected . The study selection process using PRISMA flow chart is shown in Figure , and the characteristics of the included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the elevated level of serum C‐X‐C motif chemokine (CXCL)10 has been reported as a poor prognostic marker for melanoma patients 25,26 . Serum level of CXCL10 is also reported to be elevated, and tissue CXCL10‐positive cell expression was stronger in extensive, active vitiligo patients without melanoma 27 . Although the serum level of CXCL10 was not investigated in the present study, unfortunately, CXCL10 may have a certain association with disease progression and vitiligo expansion in such melanoma patients with vitiligo who did not show a response.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA and protein expression levels of IFN-g or type I IFN were shown to be increased in the blood samples of patients with active vitiligo compared with those of patients with stable disease or healthy controls (Briggs et al, 2011;Dwivedi et al, 2013). The IFN-specific signature or IFN-producing cells were also elevated in the blood or skin lesions (Abdallah et al, 2018;Badri et al, 1993;Bertolotti et al, 2014;Rashighi et al, 2014;Yang et al, 2015). Overall, there appears to be a strong association between IFN and melanocytes destruction as well as vitiligo development.…”
Section: Discussionmentioning
confidence: 94%